Technology generates RTL from ANSI C algorithms - Maliniak, David (Electronic Design, 2003)
Unlike earlier attempts at C-to-RTL synthesis delivered as either an EDA tool or IP, PICO technology combines parallel compiler and synthesis capabilities linked to configurable RTL IP. The combination suits PICO to designers who must build custom blocks with significant amounts of parallelism.